1999
DOI: 10.3758/bf03207686
|View full text |Cite
|
Sign up to set email alerts
|

A hypertext-based tutorial with links to the Web for teaching statistics and research methods

Abstract: An online tutorial for research design and statistics is described. This tutorial provides a way for students to learn how scales of measure, research design, statistics, and graphing data are related. The tutorial also helps students determine what statistical analysis is appropriate for a given design and how the results of the analysis should be plotted in order to effectively communicate the results of a study. Initial research suggests that students using the tutorial are more accurate in their decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Of the 35 reports, 33 each contained one independent study, one report (VanLehn et al, 2007) contained four studies, and another report (Koch & Gobell, 1999) contained two studies. The studies appeared between 1990 and 2011.…”
Section: Study Featuresmentioning
confidence: 99%
“…Of the 35 reports, 33 each contained one independent study, one report (VanLehn et al, 2007) contained four studies, and another report (Koch & Gobell, 1999) contained two studies. The studies appeared between 1990 and 2011.…”
Section: Study Featuresmentioning
confidence: 99%
“…The current study recognizes Web-based tutorials as a viable option for learning by citing studies in which students using Web-based tutorials achieved as well or better as those learning in the lecture format (Alavi, 1994;Beerman, 1996;Schutte, 1996;Koch and Gobell, 1999;Maki and Maki, 2000;Andrewartha and Wilmont, 2001;Scheines, et al, 2005;Donovan and Nakhleh, 2007;Osborn, 2010;Cheng and Swanson, 2011;Sargent, et al, 2011;He, et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the students in the Web-based group outperformed their peers in the classroom environment on both the mid-term and final examinations. Koch and Gobell (1999) found that Web-based tutorials led to improved accuracy in decisions about design and the correct choice of statistics in an advanced course on research methods and statistics. Likewise, Maki and Maki (2000) found that the use of Web-based multimedia tutorials resulted in higher learning gains when compared to face-to-face lectures, with equal results found in 2003 whereby students in the Web-based version of the course did slightly better than students in the lecture version.…”
Section: Greater Student Performance With Web-based Tutorialsmentioning
confidence: 99%
“…However, as highlighted in other studies the use of Internet for educational web activities has identified a number of benefits in using it for instruction such as convenience, speed of communication, quick and remote access to information, instant feedback, and cost saving [11,12,13].…”
Section: Methodsmentioning
confidence: 99%